2019
DOI: 10.1111/hel.12661
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: Effect ofHelicobacter pylorieradication on chronic spontaneous urticaria

Abstract: Background Helicobacter pylori (HP) infection is considered to play a role in the pathogenesis of chronic spontaneous urticaria (CSU). However, the efficacy of HP eradication therapy on CSU symptom improvement has not been well established. This meta‐analysis was conducted to estimate the association between HP infection and CSU and to evaluate whether HP eradication therapy benefits patients with CSU. Material and Methods In October 2018, we searched databases for studies investigating the efficacy of HP erad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 61 publications
1
39
0
3
Order By: Relevance
“…24 Gaig's 11 27 Kim et al deduced that patients who were undergone antibiotic therapy for H. pylori eradication showed significant higher urticaria remission with or without H. pylori eradication. 28 In the present study with participation of 120 patients of CU, 40 cases (33.3%) had H. pylori infection and 80 subjects (66.6%) tested negative for H. pylori on UBT. The 40 cases (consisting of 12 male and 28 female individuals) received anti H. pylori medications, then underwent repeat UBT.…”
Section: Discussionmentioning
confidence: 67%
“…24 Gaig's 11 27 Kim et al deduced that patients who were undergone antibiotic therapy for H. pylori eradication showed significant higher urticaria remission with or without H. pylori eradication. 28 In the present study with participation of 120 patients of CU, 40 cases (33.3%) had H. pylori infection and 80 subjects (66.6%) tested negative for H. pylori on UBT. The 40 cases (consisting of 12 male and 28 female individuals) received anti H. pylori medications, then underwent repeat UBT.…”
Section: Discussionmentioning
confidence: 67%
“…Skin-specific molecules, such as mas-related G-proteincoupled receptor member X2 (MRGPRX2) expressed by mast cells only in the skin, may also be necessary for wheal formation in urticaria. In any case, it is noteworthy that TF expression on endothelial cells, but not monocytes, may be inhibited by H 1 -antihistamines and, thus, may account for the pathomechanism of CSU refractory to H 1 -antihistamines.An association of chronic infection and CSU has been described for a long time, and the eradication of Helicobacter pylori may bring about resolution of urticaria 9. In this study, LPS and FLA-ST more efficiently enhanced TF expression than Pam3CSK4 and HKLM.…”
mentioning
confidence: 54%
“…41 Another recent meta-analysis found that in H pylori-positive patients, antibiotic treatment induced chronic spontaneous urticaria remission independently of H pylori eradication. 42 In a prospective study, 57 consecutive patients (27 pityriasis versicolor, 30 telogen effluvium) screened for anti-H pylori and anti-CagA IgG, showed significantly higher rates of H pylori positivity in the pityriasis versicolor group than in the telogen effluvium group (P < .05). The number of patients with dyspeptic complaints was also higher in the pityriasis versicolor group than in the telogen effluvium group.…”
Section: S K In D Is E a S E Smentioning
confidence: 98%
“…6 A systematic review evaluated the relationship between H pylori infection and obesity among Chinese adults. The prevalence of H pylori was 42% (95% CI, [37][38][39][40][41][42][43][44][45][46][47] and mean difference of BMI between subjects with and without H pylori infection was 0.94 (95% CI, −0.04 to 1.91). The OR value was 1.20 (95% CI, 1.13-1.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 99%